A CONCISE REVIEW OF MOSQUITO MANAGEMENT STRATEGIES AND CONTROL MEASURES - Swetha, M,; Kiran Kumar, K,; Devasena, B,; Mahalakshmi, J, (The Bioscan, 2025)
Mosquito-borne diseases affect millions of people annually across more than 100 countries, posing a significant global public health challenge. Preventing human–mosquito contact remains a critical component in the control of these vector-borne illnesses. Concerns over the environmental and health impacts of synthetic insecticides have led to a paradigm shift towards the use of botanical alternatives. Plant-derived compounds, which are biodegradable and environmentally friendly, have emerged as one of the safest and most sustainable options for mosquito and insect vector management. This review highlights the current role of botanical products as green pesticides within Integrated Mosquito Management (IMM) programs. While preliminary findings indicate the promising potential of phytochemicals as effective mosquitocides, there remains a need for further development in the extraction, isolation, and standardization of bioactive herbal compounds to ensure consistent efficacy and safety.